The interplay between ethical leadership and supervisor organizational embodiment on organizational identification and extra-role performance - Costa, Sandra (2021)
This research shows the importance of supervisor organizational embodiment (SOE) for the relationship between ethical leadership and organizational identification. Drawing on the social identity model of organizational leadership, we propose that ethical leaders promote organizational identification and subsequently extra-role performance only when employees perceive that their leader shares the values and norms of their organization. In a two-wave study and a multi-source study, our findings suggest that the benefits of ethical leadership for organizational identification and consequently extra-role performance are dependent on high levels of SOE; when it is low, ethical leadership does not foster organizational identification, rendering SOE a necessary condition for this relationship. Further, the stability of the effects using multiple research designs strengthens the robustness of our findings. Theoretical and practical implications are discussed.